Social communication in advertising - Leiss, William 1939- (Routledge, 2018)
Newly updated for the digital era, this classic textbook provides a comprehensive historical study of advertising and its function within contemporary society by tracing advertising's influence throughout different media and cultural periods, from early magazines through to social media. With several new chapters on the rise of the Internet, mobile, and social media, this fourth edition offers new insights into the role of Google, Facebook, Snapchat, and YouTube as both media and advertising companies, as well as examining the role of brand culture in the 21st century